2011
DOI: 10.9753/icce.v32.currents.18
|View full text |Cite
|
Sign up to set email alerts
|

Uncertainty of Extreme Storm Surge Estimation by High Wind Sea Surface Drag Coefficient and Future Typhoon Change

Abstract: Japan has been constructing long coastal defense since the storm surge disaster with a loss of 5,000 lives by Typhoon Vera in 1959. The defense is designed for the storm water level including the storm surge of the standard typhoon based on Typhoon Vera. Stochastic typhoon model, simulating various typhoon track and intensity with Monte Carlo method, is one of useful tools to estimate the return period. According to recent research output the return period of the storm surge of the standard typhoon is near 100… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…The statistical analysis for extreme values has become widely applied and demonstrated in many practical studies. Bernardara et al (2010), Burzel et al (2010), Dong and Ji (2010), Goda et al (2010), Jonkman et al 2010, Kawai et al (2010), Kortenhaus and Oumeraci (2010), Mendez et al (2010), Mendoza et al (2010), Mertens et al (2010), Mudersbach and Jansen (2010), Naulin et al (2010), Yasuda et al (2010), Wahl et al (2010) are found in this conference papers. Those studies discussed on regional analysis, multivariate extreme values model by copula, joint distribution of waves and surges, the resultant probability distributions by numerical simulation based on stochastic typhoon models, parameters estimation by L-moments method, flood risk analysis and non-stationary model with covariates and so on.…”
Section: Introductionmentioning
confidence: 63%
“…The statistical analysis for extreme values has become widely applied and demonstrated in many practical studies. Bernardara et al (2010), Burzel et al (2010), Dong and Ji (2010), Goda et al (2010), Jonkman et al 2010, Kawai et al (2010), Kortenhaus and Oumeraci (2010), Mendez et al (2010), Mendoza et al (2010), Mertens et al (2010), Mudersbach and Jansen (2010), Naulin et al (2010), Yasuda et al (2010), Wahl et al (2010) are found in this conference papers. Those studies discussed on regional analysis, multivariate extreme values model by copula, joint distribution of waves and surges, the resultant probability distributions by numerical simulation based on stochastic typhoon models, parameters estimation by L-moments method, flood risk analysis and non-stationary model with covariates and so on.…”
Section: Introductionmentioning
confidence: 63%